The concept of vicarious suffering in the Old Testament - Geyser-Fouchè, Ananda (HTS teologiese studies, 2019)
The concept of vicarious suffering has been used to describe some form(s) of suffering in the Old Testament. The use of this concept has, however, been a source of much debate and controversy. In this article, the meaning of the concept of vicarious suffering, its presence in the Old Testament, as well as its ‘appropriateness’ and usefulness as a heuristic term in the study of the Old Testament account of suffering is discussed. Vicarious suffering is defined as ‘suffering in place of and for the benefit of others’. The study establishes that while a number of terms and practices in the Old Testament express the idea of vicariousness, the concept of vicarious suffering finds its fullest and dramatic expression in Isaiah 52:13–53:12. Therefore, the article concludes by proposing that the concept of vicarious suffering is present in the Old Testament, particularly in Isaiah 52:13–53:12, and that it continues to be an appropriate and useful heuristic concept in the study of the issue of suffering in the Old Testament.